Study on mechanical properties of modified steel slag powder concrete after high temperature - Yang, Xiaoyong; Ye, Yanbing (Frontiers in Materials, 2025)
A study was conducted to investigate the effect of steel slag powder on the compressive strength of concrete cubes at high temperatures using 150 specimens with dimensions of 100 mm × 100 mm × 100 mm. The specimens were fabricated by incorporating steel slag powder (SS) and zeolite powder (ZP), along with varying temperatures. A cubic compression test was performed, and the effect of different factors on the maximum stress was evaluated based on the test results. The results show that adding the correct proportion of steel slag powder under ZP00 conditions significantly improves the compressive strength of concrete, with an optimal replacement rate of 10% (SS10). The compressive strength of SS10-ZP20 exhibits the most significant increase under various operational conditions, with a 30.1% enhancement compared to SS00-ZP00. Moreover, an optimal quantity of zeolite powder can effectively improve the reactivity of steel slag powder. The compressive strength of concrete decreases to different extents under various operational conditions with rising temperatures. Concrete with steel slag powder has greater strength and a denser microstructure than that with SS00-ZP00. A fitting relationship was determined based on experimental data among steel slag replacement rate, mass loss rate, and concrete compressive strength.